Job Creation and Job Destruction in a Regulated Labor Market: The Case of Austria - Florian Stahl; Alfred Stiglbauer; Rudolf Winter-Ebmer; Josef Zweimüller (Oesterreichische Nationalbank (OeNB), 2002)
We study Austrian job reallocation in the period of 1978 to 1998, using a large administrative dataset where we correct for "spurious" entries and exits of firms. We find that on average 9 out of 100 randomly selected jobs were created within the last year, and that about 9 out of randomly selected 100 jobs were destroyed within the next year. Hence, the magnitude of Austrian job flows seems to be comparable to other countries, similar to the well-known results of Davis, Haltiwanger, and Schuh (1996) for the United States. Job reallocation appears to be driven primarily by idiosyncratic shocks. However, job creation increases significantly during cyclical upswings whereas job destruction rises in downturns. We also find substantial persistence of job creation and destruction. We show that the pronounced pattern of job reallocation rates falling with firm size and age continues to hold when we use a set of controls. Finally, we show that - controlling for sector and for firm size composition - Austrian job reallocation rates are only half the rates for the U. S. This result is not surprising given the impact of tighter regulation and labor law in Austria.
Keywords: D21; J23; L11; 330; Labor Reallocation; Job Flows; Labor Market Regulation